A case-study of principal succession : the experience of a high school principal and staff - Dowding, Susan Patricia (Rhodes University, Faculty of Education, Department of Education, 1997)
This is a study of a principal succession In a non-racial, multicultural High-School in the North West Province of South Africa, formerly the independent homeland known as "Bophuthatswana". I was employed at the school at the time and am, therefore, a complete member-researcher. I use a qualitative research approach which relies mostly on in-depth interviews, individually and in groups. I chose my sample by administering a short biographical questionnaire. I have sought to establish "what is happening?" in the succession process by reporting the insights and experiences of a staff and its new principal. While I use the stage frameworks of more traditional researchers in succession to provide a coherent structure for my analysis, I use the organisational socialisation perspective extensively to analyse the insights provided by the staff and principal. Unlike other principal succession studies, I include the insights of both the principal and the staff. The organisational socialisation approach emphasises that succession is an interactive, multidirectional process. My study reinforces many of the observations of other researchers in leadership succession, whether in business or Education. However, two elements of succession emerge which appear to be unique in terms of other succession literature. These elements include the impact of socio-political events and what I call "ethno-cultural" aspects on the succession socialisation process. I provide examples of the influence these factors exert in this principal succession. This study is therefore of potential significance to administrators in both Education and business in the South African context where there are significant changes taking place in the power structures and ethnic makeup of relevant organisations. I also identify a number of areas for further research.
Keywords: Educational leadership; School principals -- South Africa